Integrated marketing communication strategy of innovation product kaptan and petrocas Pt petrokimia gresik - Agustina, Crystalia; Panuju, Redi (Universitas Dr.Soetomo, 2020)
Abstract Along with the increasingly high conditions of business competition, in communicating the products of a company it is not enough to just rely on advertising media as the sole cornerstone of the company's marketing communication, but to apply Integrated Marketing Communication so that every promotional message made reaches the public. PT Petrokimia Gresik is one of the largest agro-industry companies in Indonesia, must be able to create a good marketing communication strategy to improve the brand image of its products so that they are increasingly recognized and sought after by the public, especially farmers. The research used by researchers is a qualitative descriptive study of work procedures that have been applied by companies in building marketing communication by conducting interviews and identification of marketing and sales data for further observation using a marketing communication strategy of 4-P product mix (Product, Price, Place and Promotion) and the promotion mix (marketing mix) as a benchmark in evaluating the results and improvements that need to be done by companies to improve the effectiveness of marketing programs in an effort to increase market share and sales targets.Keywords: marketing communication strategy, 4P, marketing mix.